A Royal Isaianic Servant of YHWH? - Goswell, Gregory (Scandinavian journal of the Old Testament, 2017)
In this article I argue that the Isaianic Servant of YHWH is a non-royal figure. The main arguments are as follows. The form of Isa 42,1-4, the motifs of 42,1 and the projected role of the servant in relation to justice do not support the idea that the servant is a royal figure. Likewise, in Isa 61,1-3, the portrait drawn is that of a prophetic figure with a speaking ministry. The servant of Isaiah 40-55 and the Davidic ruler of Isaiah 9, 11 and 16 cannot be equated, for the servant’s proclamatory role precedes the founding of God’s kingdom, whereas the role of the Davidic ruler is as enforcer of justice within the consummated kingdom. The focus in Isaiah 40-66 is on God as the King who liberates his people and redeems Zion and this leaves to the servant the prophetic roles of speaking and suffering as agent of the Divine King.